The United Nations and 21st century security challenges in Colombia - Fredy Leonardo Galindo-García (Escuela Militar de Cadetes “General José María Córdova”, 2021)
Multifaceted 21st-century security challenges, such as terrorism, pandemics, illegal migration, and drug trafficking, permanently question the adequacy of both state and global organizations to guarantee general wellbeing, the rule of law, and the protection of human rights. In this sense, the United Nations (UN) has received the brunt of the criticism despite its growing responsibilities, the complexity of the threats, and its decision-making structure’s limitations. This paper examines the UN’s effectiveness in addressing Colombia’s major security challenges, suggesting that providing adequate assistance to build state capacity is key to reducing power vacuums that foster both deviant globalization and embryonic security challenges.